Interface engineering of an electrospun nanofiber-based composite cathode for intermediate-temperature solid oxide fuel cells. (1st March 2023) - Kim, Seo Ju; Woo, Deokyoon; Kim, Donguk; Lee, Tae Kyeong; Lee, Jaeyeob; Lee, Wonyoung
Abstract: Sluggish oxygen reduction reaction (ORR) kinetics are a major obstacle to developing intermediate-temperature solid-oxide fuel cells (IT-SOFCs). In particular, engineering the anion defect concentration at an interface between the cathode and electrolyte is important for facilitating ORR kinetics and hence improving the electrochemical performance. We developed the yttria-stabilized zirconia (YSZ) nanofiber (NF)-based composite cathode, where the oxygen vacancy concentration is controlled by varying the dopant cation (Y2 O3 ) ratio in the YSZ NFs. The composite cathode with the optimized oxygen vacancy concentration exhibits maximum power densities of 2.66 and 1.51 W cm −2 at 700 and 600 °C, respectively, with excellent thermal stability at 700 °C over 500 h under 1.0 A cm −2 . Electrochemical impedance spectroscopy and distribution of relaxation time analysis revealed that the high oxygen vacancy concentration in the NF-based scaffold facilitates the charge transfer and incorporation reaction occurred at the interfaces between the cathode and electrolyte. Our results demonstrate the high feasibility and potential of interface engineering for achieving IT-SOFCs with higher performance and stability. Highlights: The oxygen vacancy concentration in YSZ nanofibers is controlled by varying the Y2 O3 doping ratio. High oxygen vacancy concentration substantially facilitates the overall oxygen reduction reactions. Optimized cell exhibits a remarkable performance of 2.66 W cm −2 and 1.51 W cm −2 at 700 and 600 °C.